Pathology and Seismic Zoning of Urban Fabric (Case Study: Valiasr Town of Tabriz) - Esmail Ali Akbari; Nafiseh sadat Mirayee (نشریه جغرافیا و برنامه‌ریزی, 2016)
There is a close link between the urban fabric, seismicity and seismic pathology. Urban fabric has been affected, due not only to the physical characteristics, but also through non-physical components (functional), and effects on it. This paper attempts to identify zones and levels of seismic vulnerability zones in urban fabric of ValiasrTown, Tabriz, using descriptive data and documents method. Eight indicators (distance to fault, the quality of buildings, building density, population density, building height-to-width ratio, type of land use, level of traffic service, distance from medical centers) which have been analyzes through irreversible analysis (IHWP). Results show that 54% of the town has been located in the zone of seismic vulnerability. High building density, deficiency of green and open space, high amount of building height-to-width ratio and commercial land uses are the main characteristics of urban fabric in the vulnerable zone. Model of urban fabric distribution and vulnerable zones matches with the location of main arteries (Mokhaberat, Valiasr, Shariati, Ohadi, Moalem, Foroghi, Takhti, Parvin Etesami, Aref, Zand and Javanmehr) especially sub-passages (8-10 meters) leading to these arteries and commercial land uses in the central part (Bozorg and Bazar squares). Spatial model of seismic zone has the east-west direction and center-round. This model has shaped the direction and intensity of changes in vulnerability and has created macro pattern of pathology and seismic zoning of town in two parts: The eastern half is a zone with low risk factors and vulnerability that has the most sustainable urban fabric of town.  However, western half represents high and very high seismic instability and vulnerability. The central part of the town is the spatial center of seismic intensity of these areas.